Fungsi Satuan Polisi Pamong Praja dalam Penertiban Minuman Beralkohol di Kabupaten Timor Tengah Selatan: (Studi Fungsi Satuan Polisi Pamong Praja dalam Penertiban Minuman Beralkohol di Kabupaten Timor Tengah Selatan) - Oberlin Seobil Penu; Yosef Mario Moentero; Rafael Rape Tupen (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Often viewed as drinks that can provide tranquility and warmth to the drinker, especially during the rainy season. Drinking alcoholic beverages has even become a tradition for the people in this district. As a result of this tradition, the circulation of alcoholic beverages without or lacking permits (IP-MB) can easily proliferate. 1.To understand and analyze the implementation of the Function of the Civil Service Police Unit in Regulating Alcoholic Beverages in South Central Timor District. 2. To identify and analyze the Factors Inhibiting the Function of the Civil Service Police Unit in Regulating Alcoholic Beverages in South Central Timor District. This research was conducted within the jurisdiction of the Civil Service Police Unit in South Central Timor District, using the Juridical Empirical method. The aspects studied include the Function of the Civil Service Police Unit in Regulating Alcoholic Beverages and the Inhibiting Factors of the Civil Service Police Unit in Regulating Alcoholic Beverages in South Central Timor District. Data collection involved both Primary and Secondary data. The research findings indicate that the Function of the Civil Service Police Unit in regulating alcoholic beverages is achieved through the implementation of Standard Operational Procedures (SOP), the regulation of permits for alcoholic beverage businesses, and enforcement against violations of alcoholic beverage consumption. Factors inhibiting law enforcement regarding permits for alcoholic beverage businesses include enforcement factors, socialization factors, infrastructure factors, budget constraints, the number of competent officials, and bureaucratic complexities in permit administration.